Model Music untuk Meningkatkan Motivasi Belajar Mahasiswa - Yurni Yurni; Nurhusna Nurhusna (Universitas Batanghari Jambi, 2022)
Learning motivation is a study that continues to receive great attention, especially the factors that can influence this motivation. The academic environment plays an important role in shaping student perceptions which can then affect the quality of learning and motivation. The MUSIC motivational model developed by Jones (2009) is designed to provide a conceptual framework to help lecturers in any field to understand student learning motivation. The MUSIC model is able to answer the question of what perceptions should be assessed and how those perceptions should be assessed.